2018
DOI: 10.3390/w10040382
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Treatment of Agro-Industrial and Industrial Wastewaters: Case Studies of Cr(VI)/Second Cheese Whey and Cr(VI)/Winery Effluents

Abstract: Hexavalent chromium (Cr(VI)) was co-treated either with second cheese whey (SCW) or winery effluents (WE) using pilot-scale biological trickling filters in series under different operating conditions. Two pilot-scale filters in series using plastic support media were used in each case. The first filter (i.e., Cr-SCW-filter or Cr-WE-filter) aimed at Cr(VI) reduction and the partial removal of dissolved chemical oxygen demand (d-COD) from SCW or WE and was inoculated with indigenous microorganisms originating fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The crystal’s dimensions, the concentration factor and the qualitative properties corresponded to data provided in literature for lactose obtained from conventional cheese whey. The authors concluded that the results can be used to implement the crystallization process for manufacture of lactose from SCW [ 98 ].…”
Section: Proposed Methodologies For Valorization Of Second Cheese Whey (Scw)mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal’s dimensions, the concentration factor and the qualitative properties corresponded to data provided in literature for lactose obtained from conventional cheese whey. The authors concluded that the results can be used to implement the crystallization process for manufacture of lactose from SCW [ 98 ].…”
Section: Proposed Methodologies For Valorization Of Second Cheese Whey (Scw)mentioning
confidence: 99%
“…Zeolite nitrogen from SCW can be a fertilizing agent [21] Results indicate that the agro-industrial wastewater could be used as a carbon source for Cr (VI) reduction [98] Production of a ready to drink beverage produced from SCW with fruit puree…”
Section: Continuous Flow Column Experimentsmentioning
confidence: 99%
“…There are a number of conventional techniques for Cr(VI) removal from industrial wastewaters and aqueous solutions, such as chemical precipitation, absorption, biosorption, ionexchange, electrochemical method etc. However, these methods have major drawbacks such as low affordability, difficult application, and not being environmentally friendly [11,12]. Membrane-based filtration technologies like reverse osmosis (RO) and nanofiltration (NF) have some advantages like high efficiency and ease of use [13], and have been extensively applied for the removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Using a pilot-scale biological trickling filters in series with different operating conditions, Tatoulis et al co-treat hexavalent chromium (Cr(VI)) with second SCW or winery effluents. The authors concluded that the agro-industrial wastewater could be used as a carbon source for Cr(VI) reduction, while the use of two trickling filters in series could effectively treat both industrial and agro-industrial wastewaters with very low installation and operational costs[90].Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 20 April 2021 doi:10.20944/preprints202104.0545.v1…”
mentioning
confidence: 99%